Rancang Bangun Sistem Informasi E-Commerce Gerai Hastani Kabupaten Banyuwangi Berbasis Website - Cholifah, Cholifah; Baijuri, Achmad (Fakultas Sains dan Teknologi, Universitas Ibrahimy, 2024)
Banyuwangi Regency, which is known as one of the agricultural centers in East Java Province and on a national scale, has very high agricultural potential. Even though agricultural products in this region are abundant, many farmers in this area still face economic difficulties. This is due to the long marketing chain, which results in the accumulation of high profits by intermediaries. As a result, the prices received by farmers as producers and those paid by final consumers have significant differences. To overcome this problem, an effective marketing strategy is needed. The Department of Agriculture and Food has introduced the innovation